2021
DOI: 10.1038/s41525-021-00217-5
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the multi-omics atlas of the exosomes released by human lung adenocarcinoma stem-like cells

Abstract: Lung adenocarcinoma is heterogeneous and hierarchically organized, with a subpopulation of stem-like cells (CSCs) that reside at the apex of the hierarchy, in which exosomes act as important mediators by transporting specific molecules among different cell populations. Although there have been numerous studies on tumor exosomes, the constituents and functional properties of CSC-derived exosomes are still poorly characterized. Here we present a detail transcriptome and proteome atlas of the exosomes released by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 65 publications
0
41
0
Order By: Relevance
“…Increasing research has demonstrated that the leading cause of poor prognosis for LUAD [7] is the presence of LUAD stem cells [8], which could initiate and sustain primary and metastatic cancer relapse and growth [9]. Previous evidence [10] and our most recent studies [11,12] showed that ALDH+ H1975 LUAD cells (LSCs) display strong CSC-like properties [13] and act as LSCs to influence the formation of a tumor niche, tumor initiation, and recurrence [7]. Our most recent study revealed that LSCs have the capacity for self-renewal and differentiation, which facilitates the generation of tumor cells and promotes tumor growth [11], recurrence, and metastasis.…”
Section: Introductionmentioning
confidence: 73%
“…Increasing research has demonstrated that the leading cause of poor prognosis for LUAD [7] is the presence of LUAD stem cells [8], which could initiate and sustain primary and metastatic cancer relapse and growth [9]. Previous evidence [10] and our most recent studies [11,12] showed that ALDH+ H1975 LUAD cells (LSCs) display strong CSC-like properties [13] and act as LSCs to influence the formation of a tumor niche, tumor initiation, and recurrence [7]. Our most recent study revealed that LSCs have the capacity for self-renewal and differentiation, which facilitates the generation of tumor cells and promotes tumor growth [11], recurrence, and metastasis.…”
Section: Introductionmentioning
confidence: 73%
“…Most often, however, they can be envisaged according to general criteria. CSCs share some properties with MSCs, including broad proliferation and activation of various signaling processes [ 18 , 19 , 20 , 34 ]. Relevant to CSCs are the cellular cross-talks also involving, together with stem cells, non-cancer cells accumulated at the niches [ 15 , 16 , 24 , 25 , 35 ] ( Table 1 ; Figure 1 ).…”
Section: Cscs and Their Evs Are Essential For Cancer Initiation And Its Processesmentioning
confidence: 99%
“…However, most key properties of CSCs are specific [ 17 , 34 ]; their modulation appears largely focused on self-renewal and multi-lineage differentiations [ 20 , 21 ], which is different from those of the MSC family. CSCs show multi-lineage properties, leading to the generation of distinct cancer subtypes [ 18 , 21 ]. Moreover, CSCs participate in many critical processes of cancer, from initiation and progression to formation of metastases, therapy resistance, and cancer relapse ( Table 1 ) [ 17 , 21 , 22 , 23 ].…”
Section: Cscs and Their Evs Are Essential For Cancer Initiation And Its Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Luo et al. 235 reported the transcriptomics and proteomics landscape of EVs derived from human LAC stem-like cells. They obtained a variety of mRNAs, circRNAs, and lncRNAs enriched in EVs through transcriptomics analysis.…”
Section: Isolation and Identification Of Evsmentioning
confidence: 99%